Repurposing of an antiasthmatic drug may reduce NETosis and myocardial ischaemia/reperfusion injury: editiorial - Amponsah-Offeh, Michael; Tual-Chalot, Simon; Stellos, Konstantinos (European heart journal, 2024)
This editorial refers to ‘Myocardial reperfusion injury exacerbation due to ALDH2 deficiency is mediated by neutrophil extracellular traps and prevented by leukotriene C4 inhibition’, by K. Yang et al., https://doi.org/10.1093/eurheartj/ehae205.Myocardial ischaemia/reperfusion injury (I/RI) remains a formidable challenge in cardiovascular medicine, necessitating a deeper understanding of the molecular mechanisms at play. Myocardial I/RI pathophysiology involves complex interactions between oxidative stress, cell death, and inflammation.1 Myocardial ischaemia often occurs in individuals who exhibit symptoms of an acute ST-segment elevation myocardial infarction (STEMI).1 The most efficient therapeutic approach for diminishing acute myocardial ischaemic injury in these patients and mitigating the extent of myocardial infarction is prompt opening of the occluded coronary artery by primary percutaneous coronary intervention. Reperfusion strategies, while being the standard therapy for acute myocardial infarction, can result in various forms of IR/I, including reperfusion-induced arrhythmias, myocardial stunning, microvascular obstruction, and thrombosis.1 Despite advances in these revascularization therapies, the extent of myocardial damage and adverse left ventricular remodelling, reflected by significant mortality (7% death at 1 year) and morbidity (22% prolonged or new hospitalization for heart failure at 1 year), compromise the survival and quality of life in STEMI patients.1,2 Therefore, understanding the pathophysiology of myocardial I/RI is critical in addressing the unmet need for novel therapeutic strategies to protect the heart and improve the clinical outcomes of these patients.
Online verfügbar: 26. April 2024
Gesehen am 23.10.2024